Law and the Christian tradition in Italy
1 online resource.
Keywords: "This volume explores a millennium-long story of law and religion in Italy through a series of 26 biographical chapters written by distinguished legal scholars and historians from Italy and around the world. The chapters range from the first Italian civilians and canonists, Irnerius and Gratian in the early twelfth century, to the leading architect of the Second Vatican Council, Pope Paul VI. Between these two book ends, this volume offers notable case studies of familiar civilians like Bartolo, Baldo, and Gentili and familiar canonists like Hostiensis, Panormitanus, and Gasparri but also a number of other jurists in the broadest sense who deserve much more attention especially outside of Italy. This diversity of international and methodological perspectives gives the volume its unique character"--